2014
DOI: 10.1007/s10368-014-0285-8
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal policy, net exports, and the sectoral composition of output in Greece

Abstract: This paper investigates the effects of fiscal policy shocks on net export performance and the sectoral composition of output in Greece in the post 2000 period. A reduction in government spending (or a tax hike) exerts a negative response on output which reduces import demand. A cut back in government spending boosts exports through the labour cost competitiveness channel further improving net exports. Tax hikes in particular on social security contributions and other indirect taxes reduce export performance. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
(31 reference statements)
2
7
0
1
Order By: Relevance
“…The duration effect is the same (4 years), but it is stronger in the case of government purchases, the change of which is the only important instrument of fiscal policy when it comes to exports. Again, the results confirm the conclusion by [6,8,21,30].…”
Section: Levelsupporting
confidence: 89%
See 2 more Smart Citations
“…The duration effect is the same (4 years), but it is stronger in the case of government purchases, the change of which is the only important instrument of fiscal policy when it comes to exports. Again, the results confirm the conclusion by [6,8,21,30].…”
Section: Levelsupporting
confidence: 89%
“…These results are in line with Marato and Mulas Granados [21] who emphasize the expenditure based fiscal austerity approach and also with Ali Abbas et al [2] who find a stronger current account response to fiscal policy changes in the emerging countries. The same effects for increases in government spending are reported in [7,8,14], while Beetsma et al [6] and Tagkalakis [30] find the same effects for government purchases in the case of the ten EU countries and Greece. The same analysis was then performed on two subsamples: a group of countries with the flexible exchange rate and for the countries with the fixed exchange rate regime.…”
Section: Levelsupporting
confidence: 55%
See 1 more Smart Citation
“…In fact, most of the relevant empirical studies about Malaysia discuss the fiscal multiplier in Malaysia and the reactions of economic variables at an aggregate level to a fiscal policy shock. The impact of fiscal policy on the sectoral output was examined by Tagkalakis (2014) and Monacelli and Perotti (2008). They examined the data of traded and non-traded goods in Greece and the United States, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Raff o (2008) showed that trade fl uctuations were driven by consumption smoothing while generating pro-cyclical net trade in goods. Tagkalakis (2015) examined the case of Greece in the post 2000 period and found that a cut back in government spending boosts exports through the labour cost competitiveness channel further improving net exports. Prilepskiy (2017) analysed the case of Russia and demonstrated that in the medium term, low quality of the institutional environment in Russia hinders maintaining momentum for exports and import substitution associated with the depreciation.…”
Section: Introductionmentioning
confidence: 99%